2023
DOI: 10.3389/fmicb.2022.1108890
|View full text |Cite
|
Sign up to set email alerts
|

The microbial communities and natural fermentation quality of ensiling oat (Avena sativa L.) harvest from different elevations on the Qinghai-Tibet Plateau

Abstract: IntroductionEnsiling whole-crop oat (Avena sativa L.) has attracted a growing interest in the Qinghai-Tibet Plateau. The study aimed to investigate the microbial community and chemical composition of fresh and ensiling oat harvested from six different elevations of the Qinghai-Tibet Plateau.MethodThe oat (A. sativa L. cv. Qingyin No. 1) was planted in six different sites across Qinghai-Tibet Plateau (BM, Bomi County; BY, Bayi County; DZ, Dazi County; BR, Biru County; SC, Suo County; SN, Seni County), where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Before ensiling, Filobasidium and Ustilago were detected in fresh oat with high abundances, however, they noticeably declined after 60 days of fermentation. This is in accordance with the findings of previous studies, which also found that a relatively high level of Filobasidium appeared in fresh oats and decreased with the ensiling process (Bao et al., 2023 ; Li, Chen, et al., 2022 ). According to the report of Ökmen et al.…”
Section: Discussionsupporting
confidence: 93%
“…Before ensiling, Filobasidium and Ustilago were detected in fresh oat with high abundances, however, they noticeably declined after 60 days of fermentation. This is in accordance with the findings of previous studies, which also found that a relatively high level of Filobasidium appeared in fresh oats and decreased with the ensiling process (Bao et al., 2023 ; Li, Chen, et al., 2022 ). According to the report of Ökmen et al.…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is consistent with the results of previous reports Truyens [ 27 ]. For the study of Achnatherum inebrians [ 33 ], Elymus sibiricus and Elymus dahuricus [ 32 ], Avena sativa L. [ 34 ], etc., it was found that the dominant bacteria of most plants were Bacillus. Through the study and analysis of culturable bacteria in the Achnatherum splendens seed belt, it was found that they also had diversity.…”
Section: Discussionmentioning
confidence: 99%